Design and development of nitrate-nitrite based molten salts for concentrating solar power applications. (August 2019) - Villada, Carolina; Jaramillo, Franklin; Castaño, Juan Guillermo; Echeverría, Félix; Bolívar, Francisco
Highlights: Thermodynamic simulation of nitrate mixtures is presented. The effect of LiNO3 in the thermo-physical properties was studied. New nitrate-nitrite based molten salts were developed. Comparison between Hitec and three ternary reciprocal mixtures. Storage capacity per KW-h for Hitec and new molten salts was estimated. Abstract: This study presents new alternative molten salt mixtures as energy storage media in concentrating solar power technologies. The commercial Hitec mixture and new ternary reciprocal mixtures with lithium nitrate were studied. Various techniques were used in order to examine the thermal and rheological properties of the selected salt mixtures. The results show for the new mixtures a decrease of the melting temperature up to 65 °C lower than the commercial Hitec. Thermal stability under a nitrogen atmosphere is stable up to at least 600 °C for all the mixtures analyzed. With the lithium nitrate addition, the heat capacity is improved and the viscosity at the critical temperature (close to the solidification temperature) is reduced. The evaluation of the melting point, heat capacity, thermal stability and viscosity showed that the new molten salt mixtures have great potential applications in thermal storage systems despite the cost of lithium nitrate. The operational range can be extended since a larger Δ T reduces the salt amount and hence the capital costs of a thermal energy storage system.